Analysis of Digital Literacy Sources to Identify The Relationship Between Population Income, Socio-Economic and Subjective Well-Being - Tanti Widia Nurdiani; Nofirman; Muhammad Reza Aulia; Gede Wirabuana Putra; Iwan Henri Kusnadi (Jurnal Sistim Informasi dan Teknologi, 2024)
This research aims to analyze income inequality and subjective welfare in a region. This study uses microdata from household surveys to calculate income inequality. We conducted this survey using an identical questionnaire with a sample of adults. The sample size is around 100. One of the main findings of this study is that regions that were traditionally considered to have greater inequality no longer have this attribute when compared to regional and global levels. This reflects a shift in the pattern of inequality in the region. A positive correlation was also found between income inequality and subjective well-being, as well as a curve when comparing subjective well-being inequality with products. These results suggest that there is a complex relationship between these factors in the context of inequality. However, when compared with the level of subjective well-being, there is a very negative relationship, which may indicate an individual's preference to live in areas that are more egalitarian in terms of well-being. This indicates that subjective well-being perceptions are also influenced by factors other than income, such as access to facilities and services. Although these results are interesting, it is important to remember that this study has problems and limitations in terms of the survey and methods used. Therefore, these results should be interpreted with caution and can serve as a basis for further research to understand more deeply the relationship between income inequality, subjective well-being, and other factors that influence perceived well-being.